The short- and long-term risk of stroke after herpes zoster - a nationwide population-based cohort study. - Nandini Sreenivasan (Public Library of Science (PLoS), 2013)
Background and objective Varicella zoster virus (VZV) is known to cause VZV vasculopathy, which may be associated with stroke. A recent study found an increased risk of stroke within one year of herpes zoster. We aimed to investigate the short and long-term effects of herpes zoster on the risk of stroke. Methods Using Danish national registers, we constructed a cohort consisting of all Danish adults ≥18 years old between 1995 and 2008 (n = 4.6 million; person-years of follow-up = 52.9 million). Individual-level information on prescriptions for herpes zoster antiviral treatment and diagnoses of stroke was obtained from national registers. We compared the risk of stroke in persons who had received the specific dosage of acyclovir for herpes zoster with persons who had never received antiviral treatment by Poisson regression. Results During follow-up, 2.5% received treatment for herpes zoster and 5.0% were diagnosed with stroke. Individuals who had received medication had a 127% (95% CI 83-182%) increased risk the first two weeks, 17% (CI 9-24%) between two weeks and one year, and 5% (2-9%) after the first year. The increased risk was greatest in the youngest age group (<40). To control for healthcare-seeking behaviour, we conducted parallel analyses investigating the risk of selected fractures after herpes zoster and found no similar increased risks. Conclusions This large nationwide cohort study found an increased risk of stroke after treatment for herpes zoster. Although the short-term risk was particularly high, we cannot rule out the possibility of a small but important long-term risk.